Pitting corrosion of type 304 stainless steel and sulfate inhibition effect in chloride containing environments - Raul Leandro Davalos Monteiro; Satria Dwi Ananda (Revista Tecnológica)
A detailed experiment of pitting corrosion phenomena of type 304 stainless steel in chloride environments was performed; two experimental methods potendiodynamic and galvanostatic testing were carried out in samples of type 304 stainless steel in order to understand the effect of pit depth and the stable pitting behavior. For both tests, the environment was a solution of 0.1 M NaCl, and the potential values were measured in a reference to a Saturated Calomel Electrode (SCE) and a platinum counter electrode. The results shown that the repassivation potential in the deeper pit is lower, in simple terms, the deeper the pit the lower the re-passivation potential therefore deeper pits are more stable and those type of pits are more difficult to repassivate. The effect of sulfate ions was tested by performing a potentiodynamic polarization test in 0.1 M NaCl + 0.1 M Na2SO4 solution. the sulfate in the solution has an inhibiting effect by increasing the pitting potential which indicate a longer time for pit to be stable and reduce the pit nucleation on the sample surface hence it has less metastable pits. In the galvanostatic experiment the metastable and stable pitting behaviors are elucidated, finally it is noteworthy to conclude that type 304 is very susceptible to pitting corrosion in chloride environments and the presence of sulfate ions in the a chloride effect has a positive impact on the pitting corrosion resistance of type 304.